ECOLOGICALLY CONSCIOUS CONSUMER BEHAVIOR: STUDENT PERSPECTIVES AS A CONSUMER - Naufal Hidayah Nasution; Ihsan Hadiansah (President University, 2021)
The paper reviews the ecologically conscious consumer behavior and factor that influenced the ECCB. Since people start to realized environmental issues is very important in their life and many factors that influence. The factors examined in this study consist of Environmental Concern, Consumer Characteristic, and Ecologically Conscious Consumer Behavior. This study uses quantitative methods research design and questionnaire as survey methodology. Sampling technique used non-probability sampling and gather 207 respondents. To analyze the data, this study using regression methods with a simultaneous and partial test. The result showed that the Environmental Concern has positive influence on Ecologically Conscious Consumer Behavior. And, Consumer Characteristic has a positive influence on Ecologically Conscious Consumer Behavior. Both independent variables (Environmental Concern and Consumer Characteristic) have a good influence on the dependent variable (Ecologically Conscious Consumer Behavior) simultaneously. This research gives a better knowledge and understanding of green marketing.Keywords: Environmental Concern, Consumer Characteristic, Ecologically Conscious Consumer Behavior.